Support For Sustainable Strategic Management Using SMART Technology: A Managerial Perspective - Gabriel KOMAN; Martin HOLUBČÍK; Jakub SOVIAR (Communications of International Proceedings, 2022)
The great expansion of intelligent devices used in the fight against the current coronavirus pandemic did not occur until the advent of modern information and communication technologies, making it possible to fight the pandemic faster and more effectively than ever before. The use of intelligent (SMART) technologies in the fight against the pandemic is discussed in this paper. It focuses not only on the description of individual intelligent devices and their functionality, but also on their integration and targeted use of these devices as a support tool for management and decision-making in the healthcare sector during a pandemic. Last but not least, it points out the advantages but also the disadvantages and risks that the use of intelligent devices in healthcare brings. The functionality of the facilities in different areas such as sports and healthcare can vary in volume and can also be targeted at different types of users, such as diabetics, people recovering from a medical procedure or others, and making their lives much easier, or sports performance, which is also the primary reason for their existence in the world.
Keywords: Sustainable strategic management. Sports equipment. Intelligent technologies. SMART technology. Artificial intelligence. Internet of things. Sensor networks. Robotization.